You've always been there for me : understanding the lives of grandchildren raised by grandparents - Dunifon, Rachel E. (Rachel Elizabeth) (Rutgers series in childhood studies., 2018)
Today, approximately 1.6 million American children live in what social scientists call "grandfamilies"--Households in which children are being raised by their grandparents. In You've Always Been There for Me, Rachel Dunifon uses data gathered from grandfamilies in New York to analyze their unique strengths and distinct needs. Though grandfamilies can benefit from the accumulated wisdom of mature adults raising children for a second time, Dunifon notes, such families also face high rates of health problems as well as parenting challenges related to a large generation gap. Grandfamilies are also largely hidden in American society, flying under the radar of social service agencies, policymakers, and family researchers. This book gives family researchers a greater understanding of a unique family form, and also offers service providers, policymakers and the general public important information about the lives of an important group of American families